Mesenchymal stromal cells expressing a dominant-negative high mobility group A1 transgene exhibit improved function during sepsis. Issue 4 (13th January 2021) - Kwon, Min-Young; Ghanta, Sailaja; Ng, Julie; Castano, Ana P; Han, Junwen; Ith, Bonna; Lederer, James A; El-Chemaly, Souheil; Chung, Su Wol; Liu, Xiaoli; Perrella, Mark A
Abstract: High mobility group (HMG)A proteins are nonhistone chromatin proteins that bind to the minor groove of DNA, interact with transcriptional machinery, and facilitate DNA-directed nuclear processes. HMGA1 has been shown to regulate genes involved with systemic inflammatory processes. We hypothesized that HMGA1 is important in the function of mesenchymal stromal cells (MSCs), which are known to modulate inflammatory responses due to sepsis. To study this process, we harvested MSCs from transgenic (Tg) mice expressing a dominant-negative (dn) form of HMGA1 in mesenchymal cells. MSCs harvested from Tg mice contained the dnHMGA1 transgene, and transgene expression did not change endogenous HMGA1 levels. Immunophenotyping of the cells, along with trilineage differentiation revealed no striking differences between Tg and wild-type (WT) MSCs. However, Tg MSCs growth was decreased compared with WT MSCs, although Tg MSCs were more resistant to oxidative stress-induced death and expressed less IL-6. Tg MSCs administered after the onset of Escherichia coli -induced sepsis maintained their ability to improve survival when given in a single dose, in contrast with WT MSCs. This survival benefit of Tg MSCs was associated with less tissue cell death, and also a reduction in tissue neutrophil infiltration and expression of neutrophil chemokines. Finally, Tg MSCs promoted bacterial clearance and enhanced neutrophil phagocytosis, in part through their increased expression of stromal cell-derived factor-1 compared with WT MSCs. Taken together, these data demonstrate that expression of dnHMGA1 in MSCs provides a functional advantage of the cells when administered during bacterial sepsis. Graphical Abstract: Administration of adipose-derived MSCs expressing a dominant-negative HMGA1 transgene results in less tissue injury and inflammation during a systemic infection, while improving neutrophil phagocytosis.